CASE STUDY: WARM COMPRESSES OF LEMONGRASS IN CHILDREN WITH FEBRILE SEIZURES WITH HYPERTHERMIA - Asri Aprilia Rohman; Sri Sulastri Desi Yanti; Andan Firmansyah (Jurnal Ilmiah Keperawatan, 2023)
Febrile convulsion are seizures due to an increase in body temperature (the rectal temperature is usually more than 38oC) the cause is an extracranial process. According to the World Health Organization (WHO) in research conducted by Paudel (2018), it is estimated that in the world more than 21.65 million children have fever and more than 216,000 children die. The problem that arises is hyperthermia, one way to overcome it is to use a warm compress using lemongrass boiled water to lower body temperature. To conduct a case study with an approach to care for children with febrile convulsion with hyperthermia using the application of warm compresses using boiled lemongrass water. This study uses a descriptive case study design through a nursing care approach to children with febrile convulsion in the Jasmine care room at the BLUD RSU Banjar City. Collecting data by means of interviews, observation, physical examination, and documentation. The results of the physical examination during the assessment showed the child's body temperature was 38.5oC. Warm compresses of boiled lemongrass were implemented for 4x24 hours with the results showing a decrease in body temperature after being given a warm compress technique using lemongrass boiled water, as indicated by the evaluation results showing a normal body temperature of 37.3oC. Implementation of warm compresses using lemongrass boiled water in pediatric patients with febrile convulsion with hyperthermia nursing problems is effective in lowering body temperature.